Implementation Aes-128 Encryption For Enhanced Data Security In Central Sulawesi Provincial Inspectorate - Wahyudi, Imam; Syahrullah; Anggreni, Dwi Shinta; Laila, Rahmah (Advance Sustainable Science Engineering and Technology, 2024)
One technique to secure data is to use the Advanced Encrypt on Standard (AES) 128 method. The Advanced Encrypt on Standard (AES) method can be applied in improving data security, especially at the Central Sulawesi Provincial Inspectorate. The data in question are audit reports of BOS funds (School Operational Assistance), reports of special investigations into violations of regional finances and reports of violations of civil servant discipline (PNS). The data must have a high level of security, so that it is not easily known by irresponsible parties and will have a negative impact and be misused. The conclusion in this study was obtained that, the AES-128 algorithm can be used as an alternative to the process of improving data security, namely by encryption and decryption. The results of encryption can be guaranteed as long as the symmetry key encryption is not leaked to irresponsible parties